Export Superstars - Freund, Caroline (MIT Press, 2016)
We show that very large firms shape country export patterns. Among 32 countries, the top firm on average accounts for 14% of a country’s total (non-oil) exports, and the top five firms make up 30%. These export superstars are also important in the sectoral distribution of exports. Variation in exports from the top firm in a country explains about one-third of the variation in sectoral exports relative to income across countries, and variation in exports from the top five firms explains nearly half. Revealed comparative advantage in a sector can be created by a single firm.